2022
DOI: 10.1021/acs.joc.1c03020
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Free Copper-Catalyzed Electrophilic Nitration of Electron-Rich Arenes with Guanidine Nitrate

Abstract: A practical copper-catalyzed nitration of electron-rich arenes with trimethylsilyl chloride and guanidine nitrate is reported. A variety of nitrated products were generated in moderate to excellent yields (32–99%) at ambient temperature under acid-free, open-flask, and operationally simple conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[35][36][37][38][39] Two other main strategies [40][41][42][43][44][45][46] include (i) ipso-nitration of prefunctionalized aromatic compounds, e. g., arylboronic acids, aryl carboxylic acids, aryl halides and pseudohalides, and aryl metal compounds; and (ii) transition-metal-catalyzed C(sp 2 )À H nitration of arenes. [19,21,[47][48][49][50][51][52][53][54][55] Recent studies by several groups revealed that the use of ingeniously designed nitrate reagents or N-nitro-type reagents, e. g., 3-disulfonic acid imidazolium nitrate, [56] guanidine nitrate, [57] 1-sulfopyridinium nitrate, [58] thiourea nitrate, [59] N-nitropyrazole, [60] N-nitrosuccinimide, [61] dinitro-5,5-dimethylhydantoin, [62] and N-nitrosaccharin, [63] etc., as nitro sources, are attractive and powerful methods for nitrating arenes. Despite the effectiveness of these synthetic strategies, they also suffer from several drawbacks, including functional group intolerance originating from the use of strong acids, the requirement of prefunctionalized arenes for ipso-nitration, the use of prefunctionalized direct groups as chelating moieties for transition metal-catalyzed nitration reactions, and the use of precious metals as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] Two other main strategies [40][41][42][43][44][45][46] include (i) ipso-nitration of prefunctionalized aromatic compounds, e. g., arylboronic acids, aryl carboxylic acids, aryl halides and pseudohalides, and aryl metal compounds; and (ii) transition-metal-catalyzed C(sp 2 )À H nitration of arenes. [19,21,[47][48][49][50][51][52][53][54][55] Recent studies by several groups revealed that the use of ingeniously designed nitrate reagents or N-nitro-type reagents, e. g., 3-disulfonic acid imidazolium nitrate, [56] guanidine nitrate, [57] 1-sulfopyridinium nitrate, [58] thiourea nitrate, [59] N-nitropyrazole, [60] N-nitrosuccinimide, [61] dinitro-5,5-dimethylhydantoin, [62] and N-nitrosaccharin, [63] etc., as nitro sources, are attractive and powerful methods for nitrating arenes. Despite the effectiveness of these synthetic strategies, they also suffer from several drawbacks, including functional group intolerance originating from the use of strong acids, the requirement of prefunctionalized arenes for ipso-nitration, the use of prefunctionalized direct groups as chelating moieties for transition metal-catalyzed nitration reactions, and the use of precious metals as catalysts.…”
Section: Introductionmentioning
confidence: 99%